Kesadaran Hukum Masyarakat Terhadap Pencatatan Poligami di Nagari Salareh Aia Palembayan - Kamelia Tanjung (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study examines the level of legal awareness among the community of Nagari Salareh Aia, Kecamatan Palembayan, regarding the registration of polygamous marriages. Polygamy, regulated under Islamic law and Indonesian legislation, permits a maximum of four wives under conditions of justice, court approval, and the consent of the first wife. The research employs a qualitative approach with field research and purposive sampling of 20 informants, who were interviewed in-depth to gather data on knowledge, understanding, attitudes, and legal behavior. The findings indicate that although the community is aware of the obligation to register polygamous marriages, their understanding and attitudes toward the legal requirements are weak. Many polygamous unions remain unregistered due to a lack of procedural knowledge and limited willingness, including disapproval from the first wife. This situation results in legal uncertainty concerning the status of wives and children and threatens family stability. The study concludes that the legal awareness of the community regarding polygamy registration is low, highlighting the need for enhanced legal socialization and education to ensure polygamy is practiced in accordance with prevailing laws for the sake of justice and protection of all parties involved.